2020
DOI: 10.1088/1361-6463/abaf24
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study by density functional theory calculations of decomposition processes and primary products of C5F10O with moisture content

Abstract: C5F10O has been widely studied as a great potential alternative gas to SF6, a most potent industrial greenhouse gas that is predominantly used as an insulating medium in electrical equipment, due to its excellent insulation properties and environmental characteristics. Several experimental and theoretical attempts have been made and have obtained valuable results in the last five years. However, few researchers have thoroughly investigated the decomposition mechanism and the main decomposition pathways of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Then the formation energy under O-rich condition results show that the Cr-doped system is thermodynamically stable, and device Cr_Type-b has the strongest electronic transfer capacity under zero bias among all half-metal devices. On the basis of density functional theory (DFT) [38][39][40] and nonequilibrium Grimm function (NEGF) [41][42][43], we construct devices along the y and z directions of the Cr-doped system respectively, and study their transport properties. The calculated results display that the Cr-doped system has close to 300% AMR in different transport directions, perfect spin filtering efficiency, and NDR effect.…”
Section: Introductionmentioning
confidence: 99%
“…Then the formation energy under O-rich condition results show that the Cr-doped system is thermodynamically stable, and device Cr_Type-b has the strongest electronic transfer capacity under zero bias among all half-metal devices. On the basis of density functional theory (DFT) [38][39][40] and nonequilibrium Grimm function (NEGF) [41][42][43], we construct devices along the y and z directions of the Cr-doped system respectively, and study their transport properties. The calculated results display that the Cr-doped system has close to 300% AMR in different transport directions, perfect spin filtering efficiency, and NDR effect.…”
Section: Introductionmentioning
confidence: 99%
“…The larger the molecular orbital gap value is, the higher the chemical stability is [1]. The calculations of ionization energy (IE), electron affinity (EA) and molecular orbital energy gap (E G ) are expressed as the following expressions [10]. ( ) ( )…”
Section: Dielectric Strength Environmental Characteristics and Safety...mentioning
confidence: 99%
“…Although their ionization energies are relatively high, it can be found that both CF 3 H and CF 3 OH are less electronegative than HFO-1234ze(E) by comparing the electron affinity. CF 3 H is a greenhouse gas with a GWP value of 11,700 times that of CO 2 [10].…”
Section: Dielectric Strength Environmental Characteristics and Safety...mentioning
confidence: 99%
“…At present, several potential environmentally friendly alternative gases to SF 6 mainly include Novec 4710 (C 4 F 7 N), Novec 5110 (C 5 F 10 O) and HFO-1336mzz(E), which has been attracted considerable attention. Recently, a great deal of research has been carried out on C 4 F 7 N [9][10][11] and C 5 F 10 O [12][13][14], such as insulation properties, decomposition properties, and gas-solid compatibility, etc. In contrast, the properties of HFO-1336mzz(E) have been less studied.…”
Section: Introductionmentioning
confidence: 99%